Chapter Educazione degli Adulti, dalle strategie alle urgenze. In luogo di una introduzione - Boffo, Vanna (Studies on Adult Learning and Education, 2022)
The text highlights the lines of the research crossed by Paolo Federighi in his forty-year professional career within the University of Florence and the European institutions. We take the opportunity of this perusal to problematize the discipline, Adult Education, through a semantic and lexicographic analysis which aims to bring to light the history and theory of Adult Education from its beginnings in Italian society and culture in the period after the Second World War to date. The pedagogical-educational knowledge forming the building blocks of the discipline cannot be separated from scientific research and methodological results. The second part of the essay sets out to understand which research methodology can be more appropriate to respond to the needs of a constantly evolving and rapidly changing civil society. The third and fourth parts reflect on a human and scientific itinerary always pointed towards the lodestar of educational innovation and educational transformation.